NUMERICAL STUDY OF NATURAL CONVECTION IN A CAVITY WITH WAVY VERTICAL WALLS (Journal of Engineering, 2008)
This paper describes a numerical study of natural convection heat transfer and fluid flow characteristics inside a cavity with wavy vertical walls. The bottom wall is heated by spatially varying temperature and other three walls are kept at cooled temperature. Governing equation was discretized using the finite volume-method with staggered variables arrangement in curvilinear coordinates. Two geometrical configurations were used in this study for symmetrical and unsymmetrical wavy vertical walls (total of 132 cases) for range of Ra=100 to 106 and fixed Prandtl number (0.71). The effects of the wave geometry, wave amplitude, number of undulation, and Rayliegh number on flow behavior, thermal field, local Nusselt number and Nusselt number ratio (NNR) factor have been studied. Streamline, velocity vector, and isothermal contour are used to present the corresponding flow and thermal field inside the cavity. The Results show that the enhanced of heat transfer rate seems to depend on geometrical configuration.